Acalculous Cholecystitis in Dengue - Kashif Rasool, Fatimah; Nageen, Ayesha; Kashif Rasool, Ahmed; Bashir, Farhat (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To assess the incidence of acute acalculous cholecystitis in patients with dengue fever and assess its association with laboratory parameters. METHODOLOGY: This cross-sectional study was conducted in Creek General Hospital, United Medical and Dental College, Karachi, Pakistan, from September 2020 to October 2021. Patients were included in the study through consecutive sampling. After their informed consent, all adult patients diagnosed with dengue fever, based on serological tests, were included in this study. Exclusion criteria were co-existing cholelithiasis, chronic liver disease, hemolytic and rheumatological disorders, metabolic syndrome, dyslipidemia, chronic kidney disease, use of oral contraceptive pills, pregnant females, enteric fever, vasculitis and recent surgery or trauma. The ultrasonographic features of these patients were recorded along with other laboratory investigations. SPSS ver 23.0 was used to analyze the data. Student t-tests and Chi-square tests were used to assess the association between the variables, and a P-value of <0.05 was considered significant. RESULTS: 248 patients with dengue fever were included in this study. More than 49% of these patients were diagnosed to have acalculous cholecystitis. Development of this condition was significantly associated with hemoconcentration, thrombocytopenia, leucopenia and transaminitis. All the patients recovered with conservative management, but the duration of hospital stay for these patients was considerably higher than in those without this condition. CONCLUSION: Almost half of the patients diagnosed with Dengue fever developed acalculous cholecystitis. These patients recovered with conservative management. KEYWORDS: Dengue, acalculous cholecystitis, hemoconcentration, thrombocytopenia, leucopenia.